2003
DOI: 10.1016/s0009-9236(03)90460-7
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S‐Methyltransferase (TPMT) Pharmacogenetics: Role of Chaperone Proteins in variant Allozyme Degradation

Abstract: Clinical Pharmacology & Therapeutics (2003) 73, P29–P29; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 0 publications
7
109
0
Order By: Relevance
“…Transcription and translation of BHMT and BHMT2 were performed with the TNT ® coupled RRL System (Promega) as described by Wang et al [15]. Briefly, 1 μg of expression construct DNA was added to 25 μL of RRL that had been treated to inhibit protein degradation, together with 2 μL T7 buffer, 1 μL T7 polymerase, 1 μL of a mixture of amino acids that lacked methionine, 1 μL RNasin and 2 μL 35 S-methionine (1000 Ci/mM, 10 mCi/mL, 0.4 μM final concentration).…”
Section: Rabbit Reticulocyte Lysate (Rrl) Translation and Degradationmentioning
confidence: 99%
“…Transcription and translation of BHMT and BHMT2 were performed with the TNT ® coupled RRL System (Promega) as described by Wang et al [15]. Briefly, 1 μg of expression construct DNA was added to 25 μL of RRL that had been treated to inhibit protein degradation, together with 2 μL T7 buffer, 1 μL T7 polymerase, 1 μL of a mixture of amino acids that lacked methionine, 1 μL RNasin and 2 μL 35 S-methionine (1000 Ci/mM, 10 mCi/mL, 0.4 μM final concentration).…”
Section: Rabbit Reticulocyte Lysate (Rrl) Translation and Degradationmentioning
confidence: 99%
“…Transcription and translation of HSD3B1 and HSD3B2 allozymes were performed with the TNT® coupled rabbit reticulocyte lysate (RRL) System (Promega), as described by Wang et al [23][24][25]. Specifically, 1 µg of expression construct DNA, together with 2 µL T7 buffer, 1 µL T7 polymerase, 1 µL of a mixture of amino acids that lacked methionine, 1 µL RNasin (Promega) and 2 µL of 35 S-methionine (1000 Ci/mM, 10 mCi/mL, 0.4 µM final concentration) (Amersham Pharmacia Biotech) were added to 25µL RRL that had been "treated" to inhibit protein degradation.…”
Section: Hsd3b1 and Hsd3b2 In Vitro Translation And Degradationmentioning
confidence: 99%
“…Several mechanisms might be responsible for these decreases in level of enzyme protein. However, the most common mechanism by which nonsynonymous cSNP affect protein quantity is accelerated degradation [23,24,39]. Therefore, in vitro degradation studies were performed with the HSD3B1 Phe96 variant allozyme that displayed a greater than 50% decrease in protein quantity.…”
Section: Hsd3b1 and Hsd3b2 Quantitative Western Blot Analysesmentioning
confidence: 99%
“…The mechanism of accelerated degradation of TPMT*2 and TPMT*3A proteins is responsible for the reduced level of TPMT proteins and thereby for the reduced catalytic ability of enzymes . More detailed studies have confirmed that in the accelerated degradation of TPMT*3A protein, through a ubiquitin-mediated system, the molecular chaperones from the family of heat shock proteins are involved (Wang et al, 2003).…”
Section: Functional Characterization Of Tpmt Allozymesmentioning
confidence: 91%